FAILED SHOWCASE OF EMPIRE?: THE GOLD COAST POLICE BAND, COLONIAL RECORD KEEPING, AND A 1947 TOUR OF GREAT BRITAIN - Plageman, Nate (International Library of African Music, 2016)
In 1947, the Gold Coast Police Band embarked on a four-month long tour of Great Britain. The event, which was organized by the Accra government and Colonial Office in London, was designed to be a carefully-scripted showcase of the Empire's merits and future prospects. As a result, the bulk of the written records that colonial officials compiled about it focused not on its actual progression or outcomes, but on their own preparations and confidence about its "inevitable” success. This article examines this pattern of colonial record keeping and looks beyond its overt declarations to analyze a series of incomplete exchanges, isolated letters, and brief references that tell a much more complicated story. Insisting that these archival fragments reveal that the tour did not go as planned, it also proposes that we can use them to engage two topics important to studies of African music during the colonial period: the state's strategic use of music and the colonial archive's utility as a source of information about past musical events.
Keywords: Colonisation; Archives; Colonial Office; African Music; Great Britain; Ghana; Accra; Colonial Archives